Energy Consumption and Economic Growth: Evidence from Post-Communist Countries - Umurzakov, Uktam; Mirzaev, Bakhodir; Salahodjaev, Raufhon; Isaeva, Arletta; Tosheva, Shakhnoza (International Journal of Energy Economics and Policy, 2020)
Current study aimed to explore the nexus between energy and economic growth in post-communist nations during 1995-2014. As an empirical model, the growth model is employed including economic complexity indicator as a measure of capabilities for exporting sophisticated products. We employ Pedroni's (1999) panel cointegration tests and Panel Dynamic OLS estimation to assess the long-term link between the variables. At 1% significance level, we confirm cointegration between energy consumption and economic growth. Panel Dynamic OLS results revealed that economic growth positively influences energy consumption in Post-Communist states. The Dumotrescu and Hurlin (2012) panel Granger causality test results discovered unidirectional causality running from economic growth to energy consumption. Economic growth causes energy consumption in post-communistic countries, confirming the conservation hypothesis. Keywords: energy, growth, Post-Communist JEL Classifications: C23, O47, Q40 DOI: https://doi.org/10.32479/ijeep.10003